Didattica per studenti con disabilità visiva: una lezione multimediale di “Metodologia della Riabilitazione” - De Piano, Angela (Studi sulla Formazione/Open Journal of Education, 2014)
This research was born with the aim of improving the logistical and educational support for university students who are visually impaired. For this purpose it has been developed a prototype of multimedia lesson concerning the field of Physical Therapy. The prototype has been tested on a representative sample of visually impaired students of the University of Firenze. Below I would like to present a description of the phases of this research, from the planning to the doing.